Case Study : Prisma Textiles Sdn.Bhd / Nur Namirah Mohd Zaki - Mohd Zaki, Nur Namirah (2020)
Nowadays, there are many entrepreneurs were created in our country, Malaysia especially among young generation. In this case study, we choose to conduct at Prisma Textiles Sdn.Bhd which produce several types of clothes such as Pelikat, Sarong and so on. The textile industry using a technological element such as printing machines. The method of SWOT analysis is used in our study to identify the problems happens. Then, the recommendation towards the improvement will be made in the company. Last but least, the conclusion will be made to summarize the finding and discussion the company